THE ACCURACY OF ENDOSCOPIC ULTRASOUND-GUIDED FINE NEEDLE ASPIRATION BIOPSY (EUS-GUIDED FNAB) CYTOLOGY FOR THE DIAGNOSIS OF PANCREATIC MALIGNANCY AT THE WOLLONGONG HOSPITAL (TWH). (February 2015) - Ward, A.; Piccardi, S.; Milenkovic, S.; Cole, V.; Dill, T.; Lochhead, A.
Abstract : Aim: To determine the accuracy of EUS-guided FNAB cytology for the diagnosis of pancreatic malignancy at TWH. Methods: Retrospective study of all cases ( n  = 53) of EUS-guided FNAB cytology of pancreatic lesions at TWH, from introduction of the procedure in February 2013 until September 2014. Patients with no histological or clinico-radiological diagnosis of malignancy and < 6 months follow-up post-FNAB were excluded ( n  = 13). Cytology findings ( n  = 40) were compared to subsequent histological and clinico-radiological diagnoses. Results: EUS-guided FNAB cytology demonstrated high accuracy in the diagnosis of pancreatic malignancy: sensitivity 88%; specificity 100%; positive predictive value (PPV) 100%; negative predictive value (NPV) 89%. The diagnostic yield was 92% (i.e., 'non-diagnostic' cytology = 8%; 3/40 cases). All cytological reports of 'atypical cells' and 67% of 'non-diagnostic' specimens were followed by a histological or clinico-radiological diagnosis of malignancy. Discussion: Diagnostic yield, sensitivity, specificity, PPV and NPV were equivalent to figures published in other studies.1–5 A patient who underwent the procedure without a cytotechnician present had 'non-diagnostic' cytology and was subsequently diagnosed with pancreatic adenocarcinoma. The authors recommend microscopic assessment of specimen adequacy during the procedure, which has been shown by other studies2, 6–8 to improve diagnostic yield, sensitivity and overall accuracy in the diagnosis of pancreatic malignancy.